Humans versus machines: the case of conversational speech recognition - Stolcke, Andreas (2017)
Recent work at Microsoft and IBM has pushed the accuracy of automatic speech recognition systems on conversational speech to a level that is on par with humans, when measured on historical government evaluation data sets. I will review the history of this task and then review a recent experiment at Microsoft to benchmark state-of-the-art recognition technology against human transcription performance. The second half of the talk will look at the question of how human and machine transcription accuracy differ quantitatively and qualitatively.
Invited talk, Afeka Conference for Speech Processing, Tel Aviv